2011
DOI: 10.1186/1752-0509-5-185
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Calvin-Benson cycle

Abstract: BackgroundModeling the Calvin-Benson cycle has a history in the field of theoretical biology. Anyone who intends to model this system will look at existing models to adapt, refine and improve them. With the goal to study the regulation of carbon metabolism, we investigated a broad range of relevant models for their suitability to provide the basis for further modeling efforts. Beyond a critical analysis of existing models, we furthermore investigated the question how adjacent metabolic pathways, for instance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…The kinetic model, a successor of the corrected Zhu model [10], [11] of the Calvin-Benson cycle, was redesigned for cyanobacteria, extended (photorespiratory pathways, glycolysis) and validated on available metabolic data from Synechococcus el. PCC 7942 [6].…”
Section: Methodsmentioning
confidence: 99%
“…The kinetic model, a successor of the corrected Zhu model [10], [11] of the Calvin-Benson cycle, was redesigned for cyanobacteria, extended (photorespiratory pathways, glycolysis) and validated on available metabolic data from Synechococcus el. PCC 7942 [6].…”
Section: Methodsmentioning
confidence: 99%
“…Our preliminary study showed that a combination of genome-scale and kinetic models improves the model accuracy by implementing minor sink reactions for adjacent pathways [8]. However, the problem of unconstrained parameter estimation remains.…”
Section: Introductionmentioning
confidence: 97%
“…There are also many other models for the Calvin cycle in the literature and it would be desirable to do a careful mathematical study of their solutions. This is particularly relevant since several errors in the literature have been discovered which had gone uncorrected for many years [6], [2].…”
Section: Discussionmentioning
confidence: 99%